Metal/covalent‐organic frameworks for electrochemical energy storage applications. Issue 5 (7th August 2021) - Chu, Jun; Wang, Yanxia; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Many renewable energy technologies, especially batteries and supercapacitors, require effective electrode materials for energy storage and conversion. For such applications, metal‐organic frameworks (MOFs) and covalent‐organic frameworks (COFs) have been recently emerged as promising candidates. Their high surface area, organized channel, and multiple functions make them highly versatile and flexible as electrodes, electrolytes, and electrocatalysts in electrochemical energy storage (EES) systems. In addition, many MOFs/COFs‐derived materials tend to possess high conductivity and diverse nanoarchitecture, and can also serve as high‐performance electrodes. In this review, we summarize the extensive potentials of both frameworks and their derivatives in a range of devices, including lithium/sodium ion, lithium‐sulfur, lithium‐oxygen batteries, and supercapacitors. In addition, we discuss the remaining challenges in this area and propose potential solutions for them as well as outline a few possible directions for further development for EES applications. Abstract : Metal/covalent organic frameworks (MOFs/COFs) have received wide attention for electrochemical energy storage (EES) due to their unique structural characteristics. Herein, we summarize the applications of MOFs/COFs and their derivatives in EES, including lithium/sodium ion, lithium‐sulfur, lithium‐oxygen batteries, and supercapacitors. Moreover, the development perspective of MOFs/COFs in EES is also outlined.